An atypical case of neurobrucellosis: intracranial mass lesion mimicking tuberculosis clinically and on imaging - Parikh Tirth Vinaykumar; Vaibhavi P Patel; Akshay Sharma; Bhupendra Singh (National Board of Examinations Journal of Medical Sciences, 2024)
Brucellosis is the most common bacterial zoonosis and it causes approx half million human infections per year worldwide. Neurobrucelosis should be considered as possible differential diagnosis when a patient presents with symptomps of neruropasychiatric spectrum and fever. We report a case of neurobrucellosis in a patient who presented with headache, vomiting and an episode of generalized tonic clonic seizure.